kinneretregionalproject : Universität Bern - Universität Bern; Helsingin yliopisto; Universiteit Leiden; Wofford College (2003)
[Dt.:] Berichte über die Ausgrabungen des antiken Kinneret, Metropole auf dem Tell el-Oreimeh (Tel Kinrot) am See Genezareth in Palästina, heutiges Nord-Israel. Teilweise gibt es Publikationen zum Download. Ansonsten Bilder und Presseartikel. Sehr informationshaltige Seite! - [Engl.:] Reports about the excavations of ancient Kinneret, metropolis on Tell el-Oreimeh (Tel Kinrot) on the waterfront of Sea of Galilee in Palestine, modern Israel. In part, there are publications to download. Further photographs and press articles. Very informative web site!